2013
DOI: 10.1016/j.ultramic.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Simulating realistic imaging conditions for in situ liquid microscopy

Abstract: In situ transmission electron microscopy enables the imaging of biological cells, macromolecular protein complexes, nanoparticles, and other systems in a near-native environment. In order to improve interpretation of image contrast features and also predict ideal imaging conditions ahead of time, new virtual electron microscopic techniques are needed. A technique for virtual fluid-stage high-angle annular dark-field scanning transmission electron microscopy with the multislice method is presented that enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Here, S/TEM electron probes also interact with the environment (gas or liquid) itself and care has to be taken to avoid uncontrolled changes of the in situ condition (local heating, ionization of gas, radiolysis damage to liquids, local chemistry/pH changes, etc.) [1,17,49,55,57,65,69,[75][76][77]143,164]. When using gaseous environments in MEMS cartridges lattice resolution in S/TEM have been reported [170], while, when using liquid environments, nanometer spatial resolution seems to be the current limit [57,69,164].…”
Section: Observe Structural Evolution Of Interfaces In Gaseous and LImentioning
confidence: 99%
“…Here, S/TEM electron probes also interact with the environment (gas or liquid) itself and care has to be taken to avoid uncontrolled changes of the in situ condition (local heating, ionization of gas, radiolysis damage to liquids, local chemistry/pH changes, etc.) [1,17,49,55,57,65,69,[75][76][77]143,164]. When using gaseous environments in MEMS cartridges lattice resolution in S/TEM have been reported [170], while, when using liquid environments, nanometer spatial resolution seems to be the current limit [57,69,164].…”
Section: Observe Structural Evolution Of Interfaces In Gaseous and LImentioning
confidence: 99%
“…To obtain in situ images with high spatial resolution using organic solvent electrolytes, the thickness of the liquid layer and electron dosage needs to be optimized. 26,89,90,[125][126][127][128] The thickness of the liquid layer usually is decided by the spacer between the top and bottom chips. However, due to the liquid-induced window bulging, the liquid cell center will be much thicker than the nominal thickness.…”
Section: Summary and Path Forwardmentioning
confidence: 99%
“…The spatial resolution drops significantly as the thickness increases, as shown in early literature. 26,89,90,127,128 The total SiN x -liquid thickness, t, can be estimated using EELS based on I/I 0 5 e (Àt/k) , 129 where k is the inelastic mean free path, I 0 is the intensity of the zero-loss peak, and I is total electron intensity. This method has been used to estimate the thickness of aqueous solutions within the liquid-cell.…”
Section: Summary and Path Forwardmentioning
confidence: 99%
“…Our simulations follow a similar procedure as in our previous work [45]. Microscope parameters are based on the 200 kV JEOL 2100F AC-STEM microscope.…”
Section: Image Simulationmentioning
confidence: 99%
“…A correction factor must be applied to these line scans in order to account for the fluid and window membrane located beneath the electrode interface which have not been included in our image simulation model. In the simulations of our previous work [45] as well as in electrode-electrolyte simulations in which these atoms are instead included, we have considered how~400-500 nm of fluid and a 50 nm silicon nitride window located below the specimen of interest influence image features. It has been found that the effect on the image is to reduce the specimen signal-to-noise (SNR) by a factor of~1.2.…”
Section: Image Simulationmentioning
confidence: 99%